Pseudo-singleton pattern and agnostic business layer for multi-engineer, synchronous, heterogeneous CAD. Issue 3 (16th April 2017) - Bowman, K. Eric; Jensen, C. Greg; Shumway, Devin
Abstract : Product development processes are currently highly serial workflows that prevent needed cycle time reduction. Multi-user synchronous CAD is already improving the parallelization of these workflows and the next step is to facilitate multi-user synchronous heterogeneous CAD. This paper proposes a pseudo-singleton design pattern and a class signature which are necessary in the business logic layer of an application architecture that affects multi-user synchronous collaboration across heterogeneous CAD clients. GRAPHICAL ABSTRACT: